The Hidden Influence of Halal Labeling and Product Knowledge on Customer Loyalty: Unraveling Religiosity's Role among Cosmetic Consumers in Malang - Roby Nur Akbar; Fatmasari Endayani; Shafa Sabrina Nafarinka; Agus Haryono (Universitas Negeri Gorontalo, 2023)
Purpose: The purpose of this study is to examine the relationship between the Halal Label, product knowledge, religiosity, and customer loyalty in the thriving cosmetics market of Indonesia.Design/Methodology/Approach: This research adopts an explanatory quantitative research design. A sample of 140 respondents was selected for data collection using the random sampling method. A closed questionnaire was used, facilitated through Google Forms. The collected data were analyzed using descriptive statistical analysis and the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach.Findings: The findings of this study demonstrate that both the Halal Label and product knowledge have a direct positive impact on religiosity. Furthermore, religiosity, product knowledge, and the Halal Label significantly influence customer loyalty. It is noteworthy that religiosity also plays an indirect role by mediating the relationship between the Halal Label, product knowledge, and customer loyalty.